(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
The text analyses the work developed by the Théâtre du Mouvement, founded in Paris in 1973, highlighting diff erentiated practices undertaken with the object and their possible relationships with puppet theatre arts and contemporary tendencies in puppet theatre. The analyses are enriched with refl ections on the pedagogical activities and activities in theatre direction developed by the author at the École Nationale Supérieure des Arts de la Marionnette — ESNAM [National Higher School for Puppet Arts], in Charleville-Mézières, France, where the author has been a lecturer since 1988. Th e work of the actor-puppeteer, its ramifi cations, and the complex relationship with the object/puppet constitute the central focus of the present study. Keywords: Theatre of movement. Theatre of objects. Theatre performance. Manipulation of objects. Manipulation of puppets.